Analisis Risiko K3 Menggunakan Metode Hazard Identification Risk Assement dan Risk Control Pada Proyek Pembangunan Bundaran Kota Palangka Raya - Azzahra, Lutfia Nur Azizah; Marlina, Sari; Putro, Dhymas Sulistyono (Lambung Mangkurat University Press, 2024)
This research is needed to prevent and reduce the number of work accidents that occur in the scope of work for the construction and renovation of the Palangka Raya City Grand Roundabout because it aims to identify potential hazards, risk assessment, and K3 control in the work environment. This requires that a proper K3 system be implemented to reduce the number of work accidents so that work productivity runs optimally. Based on the results of this analysis, there are 2 dominant hazards in the Big Roundabout construction project, and there are 4 dominant risks of work accidents. Some ways to control risks are by installing counterweights on tower faucets or car faucets, installing horizontal and vertical safety nets, K3 signs, using body harnesses when working at heights, preparing SOPs based on K3 aspects, supervising workers at each work location, and use PPE based on existing hazards and risks.